What makes workers happy: Empowerment, unions or both?. (December 2019) - van der Meer, Peter H
Does the negative effect of union membership on job satisfaction, as shown in Anglophone countries, also hold for Continental Western Europe? Given the differences in industrial relations, I hypothesize that the effect will be different. I also test hypotheses about the effect of empowerment on job satisfaction, which might explain the negative union effect, and broaden the analysis to include pay satisfaction. Analyses of European Social Survey data show that the negative union effect does not exist for Continental Western Europe and that this can be explained by empowerment of employees.